(untitled) (Bangladesh Journal of Botany, 2025)
The study aims to determine the ideal pruning time and level in order to attain excellent flowering response. The experiment consists of two treatments with four pruning time, viz. T1, T2, T3, T4 and four different levels, viz. L1, L2, L3 and L4. Results indicated that growth, flowering and yield characters were significantly influenced by pruning time and its levels. The pruning done in T2 was found better for plant height (cm), shoot length (cm), number of shoots per plant, number of buds per plant, number of flowers per plant, flowers yield per plant and longer flowering duration (days). Meanwhile in T4, maximum flower diameter (cm) and average fresh weight (g) were obtained. Additionally, in T1 pruning resulted in early bud initiation (days) and flower emergence (days). Regardless of pruning time, the level kept at 30 cm (L4) exhibited favorable growth, flowering and yield characteristics. The study demonstrated that in order to obtain, maximum rose flowers yield, the plants should be pruned at 30 cm level during second fortnight of October interval. Bangladesh J. Bot. 54(2): 349-359, 2025 June